Organocatalytic diastereoselective [3+2] cyclization of MBH carbonates with dinucleophiles: synthesis of bicyclic imidazoline derivatives that inhibit MDM2–p53 interaction. Issue 76 (3rd September 2019) - Zhu, Hong-Ping; Xie, Ke; He, Xiang-Hong; Huang, Wei; Zeng, Rong; Fan, Yang; Peng, Cheng; He, Gu; Han, Bo
Abstract : MBH carbonates were successfully applied to a stereoselective [3+3] annulation with N, C -dinucleophiles for the first time, yielding a collection of pharmacologically interesting bicyclic imidazolines which were found to inhibit MDM2–p53 binding. Abstract : An efficient organocatalytic cyclization strategy was developed to synthesize pharmacologically interesting bicyclic imidazoline derivatives. Morita–Baylis–Hillman carbonates were applied as C3 electrophiles to react with N, C -dinucleophiles for the first time, yielding the desired products in good to excellent yields with outstanding diastereoselectivities. The optically pure bicyclic imidazolines were expeditiously prepared by utilizing the readily available chiral ketene aminals as building blocks. The products were found to inhibit MDM2–p53 binding and cell proliferation. The most potent compound 5c induced the accumulation of MDM2, p53 and p21 proteins in HCT116 cells and blocked interaction between MDM2 and p53.